Wound healing approach based on excretory-secretory product and lysate of liver flukes - Anna V. Kovner; Alena A. Tarasenko; Oxana Zaparina; Olga V. Tikhonova; Maria Y. Pakharukova; Viatcheslav A. Mordvinov (Scientific Reports)
Abstract Exogenous bioactive peptides are considered promising for the wound healing therapy in humans. In this regard, parasitic trematodes proteins may potentially become a new perspective agents. Foodborne trematode Opisthorchis felineus is widespread in Europe and has the ability to stimulate proliferation of bile duct epithelium. In this study, we investigated skin wound healing potential of O. felineus proteins in mouse model. C57Bl/6 mice were inflicted with superficial wounds with 8 mm diameter. Experimental groups included several non-specific controls and specific treatment groups (excretory-secretory product and lysate). After 10 days of the experiment, the percentage of wound healing in the specific treatment groups significantly exceeded the control values. We also found that wound treatment with excretory-secretory product and worm lysate resulted in: (i) inflammation reducing, (ii) vascular response modulating, (iii) type 1 collagen deposition promoting dermal ECM remodeling. An additional proteomic analysis of excretory-secretory product and worm lysate samples was revealed 111 common proteins. The obtained data indicate a high wound-healing potential of liver fluke proteins and open prospects for further research as new therapeutic approaches.